Optochemical Control of Therapeutic Agents through Photocatalyzed Isomerization. Issue 28 (20th May 2022) - Watson, Emma E.; Russo, Francesco; Moreau, Dimitri; Winssinger, Nicolas
Abstract: A Ru(bpy)3 Cl2 photocatalyst is applied to the rapid trans to cis isomerization of a range of alkene‐containing pharmacological agents, including combretastatin A‐4 (CA‐4), a clinical candidate in oncology, and resveratrol derivatives, switching their configuration from inactive substances to potent cytotoxic agents. Selective in cellulo activation of the CA‐4 analog Res‐3M is demonstrated, along with its potent cytotoxicity and inhibition of microtubule dynamics. Abstract : Using a Ru(bpy)3 Cl2 photocatalyst a rapid trans to cis isomerization for a range of pharmacological agents based‐on an alkene core is achieved. These include combretastatin A‐4 (CA‐4), a clinical candidate in oncology, and resveratrol derivatives, allowing their selective in cellulo activation. This provides a new platform for the rapid in situ activation of unmodified pharmacological agents.